2023
DOI: 10.1039/d3qo00020f
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical difluoromethylation of alkynes: synthesis of CF2H-substituted seven-membered dioxodibenzothiazepines and dibenzazepines

Abstract: A general and efficient photochemical strategy for the difluoromethylation/radical cascade cyclization of alkynes with sodium difluoromethylsulfinate (NaSO2CF2H) has been disclosed. This system provides a straightforward access to diverse pharmaceutically appealing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…We then were curious whether the conventionally utilized CF 2 H radical sources could solely mediate the desired transformation. However, Zn(SO 2 CF 2 H) 2 , NaSO 2 CF 2 H and TMSCF 2 H, which were previously employed in radical difluoromethylative functionalizations, ,, were ineffective for the vicinal bis(difluoromethylation) while giving rise to the exclusive formation of 3a ′ (Figure E). These results highlight that both radical and anionic CF 2 H sources are necessary for the desired reactivity, and 2 is capable of fulfilling both roles within this newly established Cu-electrocatalytic system.…”
Section: Results and Discussionmentioning
confidence: 97%
“…We then were curious whether the conventionally utilized CF 2 H radical sources could solely mediate the desired transformation. However, Zn(SO 2 CF 2 H) 2 , NaSO 2 CF 2 H and TMSCF 2 H, which were previously employed in radical difluoromethylative functionalizations, ,, were ineffective for the vicinal bis(difluoromethylation) while giving rise to the exclusive formation of 3a ′ (Figure E). These results highlight that both radical and anionic CF 2 H sources are necessary for the desired reactivity, and 2 is capable of fulfilling both roles within this newly established Cu-electrocatalytic system.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Dioxodibenzothiazepine and their derivatives are an important class of N -heterocycles showing emerging interests as they widely exist in biologically active molecules and sulfonamide drug molecule. 32 Very recently (2023), Zhu, Wu, & Wu et al 33 developed an efficient method for the difluoromethylation of alkynes with the help of the photochemical reaction. The authors demonstrated that N -(2-ethynylphenyl)- N ,4-dimethylbenzenesulfonamid ( 16a ) reacted with sodium difluoromethylsulfinate ( 16b ) in the presence of 5 mol% photocatalyst eosin Y to afford the desired difluoromethylated dioxodibenzothiazepine ( 16c ) with up to 74% yield and excellent stereo-selectivity E / Z ratio of 97 : 3 (Scheme 16).…”
Section: Eosin Y-catalyzed Difunctionalizationmentioning
confidence: 99%